2021
DOI: 10.1186/s13073-021-00912-z
|View full text |Cite
|
Sign up to set email alerts
|

Detection of cryptogenic malignancies from metagenomic whole genome sequencing of body fluids

Abstract: Background Metagenomic next-generation sequencing (mNGS) of body fluids is an emerging approach to identify occult pathogens in undiagnosed patients. We hypothesized that metagenomic testing can be simultaneously used to detect malignant neoplasms in addition to infectious pathogens. Methods From two independent studies (n = 205), we used human data generated from a metagenomic sequencing pipeline to simultaneously screen for malignancies by copy n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…It is playing an important role in rare and severe infections in clinic. [7] On the 1 hand, conventional microbial culture requires pathogens to be living, corresponding growth conditions, long culture time and demanding, while morphological identification needs to provide special equipment, and laboratory physician need to have the ability to identify rare pathogens, which is obviously difficult to achieve. On the other hand, compared with the polymerase chain reaction, the huge shared gene information database of mNGS can provide rich comparative sources and reduce the difficulty of diagnosis of rare infections.…”
Section: Discussionmentioning
confidence: 99%
“…It is playing an important role in rare and severe infections in clinic. [7] On the 1 hand, conventional microbial culture requires pathogens to be living, corresponding growth conditions, long culture time and demanding, while morphological identification needs to provide special equipment, and laboratory physician need to have the ability to identify rare pathogens, which is obviously difficult to achieve. On the other hand, compared with the polymerase chain reaction, the huge shared gene information database of mNGS can provide rich comparative sources and reduce the difficulty of diagnosis of rare infections.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that gene pro les in CSF can provide valuable insights into CNS tumors [19,25,26]. Recently, researchers have found that mNGS testing of human peripheral blood, bronchoalveolar lavage uid, CSF or other body uids can offer clues for distinguishing between malignancies and infectious/in ammatory diseases [27,28,29,30,31,32]. This approach was mainly based on CNV analysis, which exhibits relatively high speci city.…”
Section: Discussionmentioning
confidence: 99%
“…The large CNVs (> 10 M) encompassing several chromosomes were unlikely to be caused by inherited disorders. Instead, these CNVs were indicative of tumor cells [ 16 ]. Although the detection of these chromosomal aberrations does not render a definitive cancer diagnosis, it prompted clinicians to conduct more focused diagnostic testing for tumors instead of infectious diseases.…”
Section: Discussionmentioning
confidence: 99%